A Study on Consequences and Growth of OTT Platform using Factor Analysis and ANOVA (Indian Journal of Extension Education, 2022)
In the face of the global COVID-19 pandemic, the over-the-top service of new generic media continues its unbelievable flight. The availability of content, easy access to various shows, ease of use, and continuity of shows require users to subscribe to OTT video streaming. This study aims to pinpoint the factors that show the consequences & growth of OTT over the traditional medium and the effect of the consequences of the OTT platform on gender & occupation. With a sample size of 200, the data was gathered from primary sources utilizing convenience sampling and a semi-structured questionnaire. The data was analyzed by using factor analysis & ANOVA. Two main factors used in were Consequences of OTT (Factor 1) and OTT growth over traditional medium (Factor 2). The variations in factors 1 & 2 were 42.59 & 15.49 respectively. As per factor analysis, factor 1 was the most important and the Cronbach alpha values of 0.852 and 0.807 respectively, reveal the reliability of the two factors. Also, Analysis of Variance (ANOVA) shows that gender & occupation have a significant effect on the consequences of the OTT platform. The online consumption of content was also found to have several negative effects on the life style of the respondents.